Paromomycin and Geneticin Inhibit Intracellular Cryptosporidium parvum without Trafficking through the Host Cell Cytoplasm: Implications for Drug Delivery - Griffiths, Jeffrey K. (American Society for Microbiology, 1998)
Cryptosporidium parvum, which causes intractable diarrhea and lethal wasting in people with AIDS, occupies an unusual intracellular but extracytoplasmic niche. No reliable therapy for cryptosporidiosis exists, though the aminoglycoside paromomycin is somewhat effective. We report that paromomycin and the related compound geneticin manifest their major in vitro anti-C. parvum activity against intracellular parasites via a mechanism that does not require drug trafficking through the host cell cytoplasm. We used both normal and transformed aminoglycoside-resistant Caco-2 or MDBK cells in these studies. Timed-exposure experiments demonstrated that these drugs inhibit intracellular but not extracellular parasites. Apical but not basolateral exposure of infected cells to these drugs led to very significant parasite inhibition, indicating an apical topological restriction of action. We estimated intracytoplasmic concentrations of paromomycin, using an intracellular bacterial killing assay, and found that C. parvum infection did not lead to increased paromomycin concentrations compared to those in uninfected cells. Global [(3)H]paromomycin uptake by Caco-2 cells was ∼200-fold higher than the estimated intracytoplasmic paromomycin concentration, suggestive of host cell vesicular uptake and concentration (as has been reported with other cell lines). However, preinfection exposure of Caco-2 cells to paromomycin did not result in subsequent inhibition of parasite development, indicating that if exogenous paromomycin enters the infected host cell vesicular compartment, it does not effectively communicate with the parasite. Thus, the apical membranes overlying the parasite and parasitophorous vacuole may be the unsuspected major route of entry for paromomycin and may be of importance in the design and discovery of novel drug therapies for the otherwise untreatable C. parvum.